Electoral political process in a democratic society as a matter of political marketing - Bokoch , Viktoriya (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES)
The article studied the connection electoral culture of the electoral process and democratic political marketing. In this context, elections are regarded as an essential attribute of the electoral political culture, which is realized in the implementation of the electoral political process. In a study of the electoral process are the following conceptual methodological approaches: institutional, sociological, socio-psychological, economic rationality, selective and metaforalny and synthetic approaches. The essence of the electoral process, from the point of view of political marketing, to the greatest extent determined by the following factors: the nature of political regimes and systems, political system and form of government, especially the ideological orientations and values; hierarchical level elections (national and local), particularly the electoral law, the specificity of the masses -media support of the electoral process, leading political actors and resources, etc.